Capillary electromigration methods for fatty acids determination in vegetable and marine oils: A review. Issue 3 (22nd November 2020) - Amorim, Tatiane Lima; Duarte, Lucas Mattos; da Silva, Erick Mendes; de Oliveira, Marcone Augusto Leal
Abstract: Fatty acids determination is of paramount importance for quality control and suitable labeling of edible oils, required by regulatory agencies in several countries, and fast methods for this determination are worldly desired. This review article aimed to explore the available analytical methods for vegetable and marine oils analyses employing CE, which can be a straightforward and faster alternative than GC methods for fatty acid determination, considering some purposes. CE usually offers the possibility of a rapid analysis with a simple preparation of the sample, without requiring specific columns, which are inherent advantages of the technique. Instrumental conditions and the key points about fatty acids determination employing the technique are highlighted, and the main challenges and perspectives are also approached. Potential use of CE for edible oil analyses has been demonstrated for research and routine, which can be of interest for industries, regulatory agencies, and edible oil researchers. Therefore, we have explored the analytical approaches described in the last decades, intending to spread the interest of CE methods for fatty acid monitoring, label accuracy assessment, and food authenticity evaluation of edible oils.